1999
DOI: 10.1037/0735-7044.113.5.1042
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the immune–endocrine system with lipopolysaccharide reduces affiliative behaviors in voles.

Abstract: In Experiment 1, individually housed male meadow voles (Microtus pennsylvanicus) and prairie voles (Microtus ochrogaster) were injected with lipopolysaccharide (LPS) and exhibited the expected decrease in testosterone and increase in corticosterone and interleukin-1beta concentrations 3 hr later, indicating activation of the endocrine and immune systems. In Experiment 2, LPS- and saline-injected males were tethered in a 3-chamber partner preference apparatus. The time females spent in each chamber with a male,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 38 publications
0
17
1
Order By: Relevance
“…For instance, interleukin-1 treatment inhibits sexual behavior in female, but not male rats, while concomitantly decreasing locomotory activity in both sexes (Yirmiya et al, 1995). In microtine voles (Microtus), males paired with females are less responsive to LPS challenge than males housed alone (Klein and Nelson, 1999). These sex differences may allow males to optimize reproductive potential, especially if mating opportunities are limited.…”
Section: Social Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, interleukin-1 treatment inhibits sexual behavior in female, but not male rats, while concomitantly decreasing locomotory activity in both sexes (Yirmiya et al, 1995). In microtine voles (Microtus), males paired with females are less responsive to LPS challenge than males housed alone (Klein and Nelson, 1999). These sex differences may allow males to optimize reproductive potential, especially if mating opportunities are limited.…”
Section: Social Contextmentioning
confidence: 99%
“…These reproductive activities are suppressed in favor of increased sleep for recruitment of additional resources to combat infection (Kent et al, 1992;Dantzer, 2001). Acute phase responses also proximately inhibit the hypothalamo-pituitarygonadal axis (Rivier, 1990;Bosmann et al, 1996;Klein and Nelson, 1999), leading to a rapid decline in sex steroid levels. Furthermore, these life-history costs may persist until the animal has fully recovered from infection (Hart, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Because of constant coevolutionary cycles between host and parasite, genes for resistance never reach equilibrium, and thus can sustain continual variation and selection. It is not yet possible to ascertain whether either of these scenarios (or both simultaneously) have played a role in mate choice of rats.Yet, it is interesting that female rodents detect and avoid males infected with a variety of parasites, including ectoparasites, protozoans, nematodes and bacteria (Ehman and Scott, 2002; Kavaliers et al, 2006; Kavaliers et al, 2005a; Kavaliers et al, 2005b; Kavaliers and Colwell, 1992; Kavaliers and Colwell, 1995; Kavaliers et al, 1998a; Kavaliers et al, 1998b; Kavaliers et al, 2003;Klein and Nelson, 1999;Willis and Poulin, 2000;Zala et al, 2008). Female rodents have evolved dedicated neural machinery that serves to detect odors emanating from infected individuals and to generate an aversive response.…”
mentioning
confidence: 99%
“…One mechanism by which females can alter offspring phenotype is by producing stress-induced hormones (Spencer and Robinson, 1992). Several studies have shown that immune activation may affect corticosteroid production (Rivier et al, 1989;Klein and Nelson, 1999;Owen-Ashley et al, 2006;Adelman and Martin, 2009). Maternal corticosterone levels during development have been shown to affect offspring behaviour, morphology, growth, dispersal, sex and survival (Glickman et al, 1987;De Fraipont et al, 2000;Groothuis et al, 2005;Love et al, 2005).…”
Section: Research Articlementioning
confidence: 99%